Improvement of the Mechanical Behavior of Composite Materials with Different Binders Based on Local Plant Fibers Alfa and Diss - Belkhir, Zohra; Merzoud, Mouloud (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Concerned about the environmental and economic impact, composite materials are increasingly used in the construction sector. Indeed, the use of plant fibers as reinforcement in construction materials have been the subject of several researches in recent years; the main motivation is the weight gain combined with high mechanical characteristics. The objective of this research concerns the study of the physicomechanical properties of composite materials with cement and clay matrices reinforced with Alfa and Diss fibers with dimensions ranging from 2 to 8 cm.
Keywords: composite materials; mechanical properties; natural fibers; Alfa; Diss; cement; clay; materiały kompozytowe; właściwości mechaniczne; włókna naturalne; glina